POET PRAFULLA KUMAR MISHRA’S THINKING BASED ON SOCIAL PROBLEMS IN HIS POEMS - Alisha Biswal, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Prafulla Kumar Mishra was born in a traditional Bramhin family at the district of Puri in the state of Odisha on 20th Feb 1954. According to the Indian tradition, he has born in his maternal grandmother’s house. His mother’s name was Srimati Pramila Sundari Devi, who was an ideal teacher and his father is Sri Kashinath Mishra,is a renowned advocate at Puri district. He passed his childhood under the care of his parents, families, paternal and maternal grandmothers. As a result of which deep liking towards Indian culture and tradition were developed in him with the super source of inspirations. On the other-hand, he hailed from a highly educated family, as a consequence he is inherited a habit of learning from his childhood days. His father Kashinatha Mishra, working as a famous social worker in Puri district, who is the life-long inspiration for him. He is now retiring as a professor of Sanskrit department of Utkal University, BBSR. And before since 4 yr. Now he is working as a chancellor of DRPC Agriculture University, Bihar......